Draft Genome Sequence of Cylindrospermopsis sp. Strain CR12 Extracted from the Minimetagenome of a Nonaxenic Unialgal Culture from a Tropical Freshwater Lake - Mohamed Nor, Nur Hazimah (Genome Announc, 2016)
Cylindrospermopsis is known to be one of the major bloom-forming cyanobacterial genera in many freshwater environments. We report here the draft genome sequence of a tropical Cylindrospermopsis sp. strain, CR12, which is capable of producing the hepatotoxic cylindrospermopsin.